Beyond buzz : the next generation of word-of-mouth marketing - Kelly, Lois, 1955- (AMACOM, 2007)
This is the first book on buzz or word-of-mouth marketing to focus on the message - not just the mechanics - involved in a successful campaign. Both innovative and practical, it is filled with insightful examples of conversational marketing at work in real campaigns. Kelly's articles have been published in "USA Today", "BrandWeek", "The Wall St. Journal", "Advertising Age", and "Adweek", She speaks frequently on marketing and communications to professional organizations like the American Marketing Association and The Conference Board. Kelly's extensive experience has involved working with both larger, more established organizations as well as smaller startups - and the techniques she includes here can work for any organization